Source Width of Frontal Phantom Sources: Perception, Measurement, and Modeling - Matthias FRANK (Archives of Acoustics, 2013)
Phantom sources are known to be perceived similar to real sound sources but with some differences. One of the differences is an increase of the perceived source width. This article discusses the perception, measurement, and modeling of source width for frontal phantom sources with different symmetrical arrangements of up to three active loudspeakers. The perceived source width is evaluated on the basis of a listening test. The test results are compared to technical measures that are applied in room acoustics: the inter-aural cross correlation coefficient (IACC) and the lateral energy fraction (LF). Adaptation of the latter measure makes it possible to predict the results by considering simultaneous sound incidence. Finally, a simple model is presented for the prediction of the perceived source width that does not require acoustic measurements as it is solely based on the loudspeaker directions and gains.